Case Report: Single-cell RNA sequencing reveals cellular and molecular mechanisms in newborn cardiac hemangioma formation - Li, Tiange; An, Qi; Luo, Shuhua; Li, Yifei (Frontiers in Cardiovascular Medicine, 2025)
Primary cardiac hemangiomas are extremely rare benign tumors, with limited molecular characterization available. This study investigated a case of mixed-type intracardiac hemangioma in a 17-day-old female neonate, initially detected via prenatal echocardiography and confirmed by postoperative histopathology. The right atrial mass (1.7 × 2.0 × 2.1 cm) was surgically resected, and 1-year follow-up, which included transthoracic echocardiography every 3 months and cardiac MRI every 6 months, showed no recurrence and normal cardiac function. Single-cell RNA sequencing was performed on the tumor tissue, yielding 4,888 high-quality cells after quality control. These cells were classified into 9 distinct types, with fibroblasts/myofibroblasts and smooth muscle cells accounting for nearly half the population. Endothelial cells were subdivided into two clusters: Cluster 1, enriched in immune inflammation, cell adhesion, and signal transduction. And Cluster 2, focused on mitochondrial energy metabolism and ribosome biogenesis. InferCNV analysis revealed relative genomic stability, with only minor copy number variations on chromosome 13 in Cluster 1, supporting the tumor's benign nature. Cell communication analysis identified Cluster 1 as the primary effector cell in hemangioma formation, receiving VEGF signals mainly from myeloid-derived suppressor cells and common myeloid progenitors, while also driving collagen synthesis-related pathways. This study provides critical insights into the cellular and molecular mechanisms of cardiac hemangiomas, filling gaps in current understanding of this rare tumor.